Knowledge of ethnoveterinary medicine in the Province of Granada, Andalusia, Spain. - Benítez, Guillermo; González-Tejero, M. Reyes; Molero-Mesa, Joaquín (Journal of ethnopharmacology, 2012)
This paper constitutes an important contribution to the knowledge of biological resources used in ethnoveterinary practices (EVPs) in southern Europe, a territory with a clear lack of information on the subject. Aim of the study: To catalogue, analyze, and disseminate the knowledge of plant and animal use in eth- noveterinary practices in the province of Granada. Data have been analyzed to highlight the similarities between ethnoveterinary practices and human ethnopharmacology for the same study area. Methodology: Information was gathered through open and semi-structured interviews with local people, mainly elderly shepherds and farmers, in the western part of the province. The primary data have been supplemented with information on EVPs from previous ethnobotanical works for the province. Data were gathered using the same field methods. Results: A total of 88 ethnoveterinary uses are documented for the treatment of 24 animal conditions. Of these, 82 uses involve 60 different plant species. Over three-quarters of these plants are also used for some human conditions in the same study area. Moreover, 6 animal species were catalogued for 6 other ethnoveterinary uses; four of these species were also used for similar conditions in humans. Ritual and health-prevention practices are also discussed. Conclusions: EVPs in southern Spain involve a high number of species and conditions and are strongly linked to folk tradition (i.e. how local people understand certain conditions and their treatment, some- times in a ritual manner). Unfortunately, some evidence of their slow disappearance has been found.
The following values have no corresponding Zotero field: publisher: Elsevier Ireland Ltd accession-num: 22155471
Keywords: Ethnoveterinary; Granada; Spain; Veterinary medicine; Zootherapy

Pharmaceutical ethnobotany in the western part of Granada province (southern Spain): ethnopharmacological synthesis. - Benítez, G.; González-Tejero, M. R.; Molero-Mesa, J. (Journal of ethnopharmacology, 2010)
The aim of this work is to catalogue, document, and make known the uses of plants for folk medicine in the western part of the province of Granada (southern Spain). An analysis was made of the species used, parts of the plant employed, preparation methods, administration means, and the ailments treated in relation to pathological groups. Materials and methods: The work was performed in 16 municipalities within the study zone. The partici- pants were located mainly by questionnaires distributed in public and private centres. The information, gathered through semi-structured open interviews of a total of 279 people, was included in a database for subsequent analysis.Afloristic catalogue of the territorywascompiled, enabling analyses of the relevance of certain botanical families in popular medicine. Results and conclusions: Great diversity was established among medicinal species in the region. A total of 229 species of plants were catalogued for use in human medicine to prevent or treat 100 different health problems covering 14 different pathological groups. The number of references reached 1963. The popular pharmacopoeia of this area relies primarily on plants to treat digestive, respiratory, and circulatory problems, using mainly the soft parts of the plant (leavesandflowers)prepared in simpleways (decoction, infusion). An analysis of the medicinal ritual uses of 34 species and the different symptoms reflected a certain acculturation in relation to ethnobotanical knowledge in the last 20 years. Ethnopharmacological relevance: The traditional knowledge of plants was shown in relation to medicinal use, reflecting a striking diversity of species and uses, as well as their importance in popular plant therapy in the study zone. These traditions could pave the way for future phytochemical and pharmacological studies and thereby give rise to new medicinal resources.
The following values have no corresponding Zotero field: accession-num: 20226847
Keywords: Acculturation; Ethnopharmacology; Folk medicine; Granada; Medicinal plants; Spain

HUMAN-PLANT RELATIONSHIPS DURING THE COPPER AND BRONZE AGES IN THE BAZA AND GUADIX BASINS (GRANADA, SPAIN) - ARIZA, M O R (BULLETIN DE LA SOCIETE BOTANIQUE DE FRANCE-ACTUALITES BOTANIQUES, 1992)
The anthracological study of six sites in the north of province of Granada (Spain) has uncovered vegetation for the Copper Age formed by a dense oak grove belonging to the association Rhamno-Quercetum cocciferae. In the Bronze Age, the intensification of agriculture caused changes in the vegetation, reflected in the anthracological diagrams by the increase in Pinus halepensis and the decrease of Quercus ilex-coccifera, as well a decline in the woodlands and an expansion of the legumes. The different species present in the vicinity of the site (or in a greater radius), servings such specific functions as the making of tools and utensils, house construction, and firewood for the hearth or for fours, give us preliminary insights into the ways in which these populations used space and their vegetal environment
Keywords: CHARCOAL ANALYSIS; COPPER AGE; Granada; Spain

Datos sobre la vegetación silicícola de Andalucia I. - Caldera, J M Nieto; Latorre, A V Pérez; Cabezudo, B (Acta botánica malacitana, 1990)
: The phytocenologic study about climatophilous vegetation series, which inhibat on siliceous soils in Málaga, Cádiz, Sevilla and Granada (Spain), has produced the identification of six vegetation series. It is described the following new syntaxa: Smilaco mauritanicae-Quercetum rotundifOliae quercetosum suberis,Teucrio baetici-Querceturn suberis quercetosum rotundifoliae and Cytiso baetici-Arbutetum unedonis.
Keywords: Cádiz; Cork oak forests; Granada; holm oak forests; Málaga; phytosociology; Sevilla; siliceous soils; Spain; strawbwerry tree copses; vegetation series